Efficient lead sorption from wastewater by carbon nanofibers - Ahmed, Yehya M.; Al-Mamun, Abdullah; Al-Khatib, Ma'an Fahmi Rashid; Jameel, Ahmed Tariq; AlSaadi, Mohammed Abdul Hakeem Abdul Rahman (Springer, 2015)
Wastewater from many industries contains toxic metal ions, which should be removed before water is released into the environment. Many adsorbents have been developed to remove metals, but their efficiency should be improved by, e.g., increasing surface area. Here, we tested the use of carbon nanofibers synthesized on the surface of activated carbon, to remove lead ions (Pb2?). We studied the effect of carbon nanofiber dose, pH, contact time and agitation speed on the sorption capacity. The best conditions were with nanofiber dose of 0.25 g/L, pH of 5.5, contact time of 60 min and agitation speed of 200 rpm. The nanocomposite product was also used for the removal of lead from industrial wastewater. We also found a successful removal of 67 % of lead ions from semiconductor wastewater sample.